Environmental literacy profile of senior high school in Mowewe Southeast Sulawesi - Muhlis, Nur Fadhilah; Yani, Ahmad; Suryanni, Siti Darwa; Upe, Ambo (Biosfer: Jurnal Pendidikan Biologi, 2022)
Lack of awareness and human responsibility is one of the factors that have a major impact on increasing environmental problems. The purpose of this study was to describe the environmental literacy skills of class XI students of senior high school 1 Mowewe. The method used is a descriptive method with a quantitative approach. This research was conducted in the odd semester 2021/2022 academic year (September until November), at SMAN 1 Mowewe (Southeast Sulawesi, the subjects in this study were 50 students of class XI senior high school 1 Mowewe. The questionnaire was used to measure students' environmental literacy. The data were analyzed using descriptive analysis. The results showed that the indicator of knowledge was worth 59.78, the attitude indicator of students' attitudes was worth 69.18, the ability of cognitive skills to the environment was worth 74.52, and student behavior towards the environment had a value of 67.86. Based on the results of the study, it can be concluded that the environmental literacy ability of students at senior high school 1 Mowewe, namely the knowledge indicator has a value of 59.78 with a fairly good category, students' attitudes have a value of 69.18 with a good category. category, the ability of cognitive skills to the environment has a value of 74.52 with a good category, and student behavior towards the environment has a value of 67.86 with a good category.